2011
DOI: 10.1002/jbm.b.31993
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth on sutures of tendon cells derived from torn human rotator cuff

Abstract: Rotator cuff tendon pathology is proposed to account for 30-70% of all shoulder pain and surgical repair with a nonabsorbable suture is the common option for painful rotator cuff tears that have failed conservative treatment. A number of studies have suggested the beneficial effect of augmenting the repair with implants constructed from polymers used for sutures. Thus, it was of interest to investigate the affinity of tendon-derived fibroblasts, often thought to be the repairing agents of torn tendons, to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…Minimal tissue reaction and good ability to contain cells and fluids were the preliminary requisites when selecting a material for the creation of the patch. In a previous study, we have highlighted polydioxanone (PDO) as a candidate material for tendon repair because it was particularly compatible with tendon-derived cells in vitro (Hakimi et al, 2012). Moreover, it has an excellent history as an implant material even at large quantities of material, with acceptable host response and no severe inflammation (Curtis et al, 2005).…”
Section: Biocompatibility and Cell Attachment And Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimal tissue reaction and good ability to contain cells and fluids were the preliminary requisites when selecting a material for the creation of the patch. In a previous study, we have highlighted polydioxanone (PDO) as a candidate material for tendon repair because it was particularly compatible with tendon-derived cells in vitro (Hakimi et al, 2012). Moreover, it has an excellent history as an implant material even at large quantities of material, with acceptable host response and no severe inflammation (Curtis et al, 2005).…”
Section: Biocompatibility and Cell Attachment And Migrationmentioning
confidence: 99%
“…Moreover, it has an excellent history as an implant material even at large quantities of material, with acceptable host response and no severe inflammation (Curtis et al, 2005). However, despite excellent biocompatibility, PDO sutures (PDSII) displayed relatively low cell attachment in vitro (Hakimi et al, 2012). One challenge was therefore to design a PDO-based scaffold that will retain its biocompatibility but encourage cell attachment.…”
Section: Biocompatibility and Cell Attachment And Migrationmentioning
confidence: 99%
“…In addition, the probable negative effects of polyglactin 910 degradation products on regenerating tissues were demonstrated [10], with stubborn infl ammatory reaction [11].…”
Section: Resultsmentioning
confidence: 98%
“…) and PDO (Hakimi et al . ,b) have exhibited excellent cellular response and biocompatibility. Further, in vitro evaluations have also demonstrated that electrospun materials are likely to cause a lower immune response in vivo compared to the same materials processed into plain sheets (Smith et al .…”
Section: New Generation Of Rotator Cuff Patches: Synthetic Degradablmentioning
confidence: 99%
“…High concentration of lactic and glycolic acid have been found to be toxic to both tendon‐derived cells and osteoblasts, and non‐toxic concentrations decreased cell proliferation and increased differentiation in osteoblasts (Hakimi et al . ,b; Meyer et al . ).…”
Section: New Generation Of Rotator Cuff Patches: Synthetic Degradablmentioning
confidence: 99%